A case of silent invasion: Citizen science confirms the presence of Harmonia axyridis (Coleoptera, Coccinellidae) in Central America - Hiller, Thomas; Haelewaters, Danny (PloS one, 2019)
Harmonia axyridis (Coleoptera, Coccinellidae) is a globally invasive ladybird. It has been intentionally introduced in many countries as a biological control agent, whereas it has been unintentionally released in many others. Climatic factors are important in limiting the spread of H. axyridis. For example, very few records are known from tropical or desert regions. Currently, no published reports are known from Central America. Here, we report H. axyridis from Costa Rica, Guatemala, Honduras, Panama, and Puerto Rico. Specimens were either observed by the authors, discovered in dried insect collections, or retrieved from searching through online photographs available from the citizen science project iNaturalist and the photo-sharing website Flickr. These new records and the wide distribution of H. axyridis in Latin America suggest several invasion events, which have gone unnoticed until now. We stress the need for further, large-scale monitoring and show the advantage of citizen science to assess the presence of invasive alien species.
Keywords: Coleoptera; brouci; Střední Amerika; Citizen Science; zavlečené druhy; Animals; Geography; zeměpis; Central America; občanská věda; zvířata; Introduced Species